Maximizing Absorption in Photon‐Trapping Ultrafast Silicon Photodetectors. Issue 6 (31st March 2021) - Bartolo-Perez, Cesar; Qarony, Wayesh; Ghandiparsi, Soroush; Mayet, Ahmed S.; Ahamed, Ahasan; Cansizoglu, Hilal; Gao, Yang; Ponizovskaya Devine, Ekaterina; Yamada, Toshishige; Elrefaie, Aly F.; Wang, Shih-Yuan; Islam, M. Saif
Abstract : Silicon photodetectors (PDs) operating at near‐IR wavelengths with high speed and high sensitivity are becoming critical for emerging applications, such as light detection and ranging (LIDAR) systems, quantum communications, and medical imaging. However, such PDs present a bandwidth‐absorption trade‐off at those wavelengths that have limited their implementation. Photon‐trapping (PT) structures address this trade‐off by enhancing the light–matter interactions, but maximizing their performance remains a challenge due to a multitude of factors influencing their design and fabrication. Herein, strategies to improve the PT effect while enhancing the speed of operation are investigated. By optimizing the design of PT structures and experimentally integrating them in high‐speed PDs, a simultaneous broadband absorption efficiency enhancement up to 1000% and a capacitance reduction of more than 50% are achieved. Empirical equations correlate the quantum efficiency of PDs with the physical properties of the PT structures, material characteristics, and limitations of the fabrication technologies. The results that are obtained open routes toward designing cost‐effective complementary metal–oxide‐semiconductor (CMOS)‐integrated receivers. Abstract : High absorption and ultrafast operation can simultaneously be achieved in silicon photodetectors at near‐IR wavelengths using photon‐trapping (PT) structures. The experimental implementation of different PT structures enables several analytic expressions and design rules to maximize the photon absorption, reduce the device capacitance, and facilitate faster time response. These results open the routes toward designing cost‐effective all‐silicon CMOS‐integrated receivers.